Reconstituer les évolutions des espaces forestiers de l'Avesnois aux XIVe – XVIIIe siècles. Approches méthodologiques - Francesco Beretta; Claire-Charlotte Butez; Adrien Carpentier; Marie Delcourte (Bulletin du Centre d’Études Médiévales d’Auxerre)
Understanding the evolution of a forest area requires taking both time and space into account. This means providing a temporal dimension to a semi-natural object and considering that it can spatially move. In the work frame of this applied research thesis work (Afforestation policy), it has been necessary to use specific tools and to convert ancient data to a readable useful format.The SyMoGIH method (Système Modulaire de Gestion de l'Information Historique / Modular System for Historical Data Management) offers the possibility to work at different scale level (territory, landscape, place) using space and time data for each geographical elements of the Avesnois National Park. With this method, the historical analysis is spatially located at every period of time.